Is nuclear war more likely after Russia’s suspension of the New START treaty? - Tollefson, Jeff (Nature (London), 2023)
The nation has spurned a major arms-control agreement, pushing nuclear powers towards a worrying lack of regulation, says non-proliferation researcher. The nation has spurned a major arms-control agreement, pushing nuclear powers towards a worrying lack of regulation, says non-proliferation researcher. Credit: Mikhail Svetlov/Getty A Russian nuclear missile rolls along Red Square in front of red brick building and flanked by military personnel